PENERAPAN SMART PRESENTATION BERBASIS CANVA DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Wiwik Wiji Astuti; Jasmi Jasmi; Rahmat Rahmat; Basruddin Basruddin (Guru Membangun, 2023)
This research is motivated by the fact that learning media still uses old patterns or models with a very simple appearance so that it does not attract the attention of students which results in a lack of student motivation in teaching and learning activities, to overcome this motivation problem as educators feel it is very necessary to develop digital learning media through research class action with the title of using Canva-based smart presentations in increasing student learning motivation. The purpose of this study was to describe the application of Canva-based smart presentations in increasing learning motivation. The research subjects in this classroom action research were fifth semester students at Patompo University with a total of 9 students. Methods of data collection using observation and interviews, data analysis techniques used by using classroom action research techniques. The results showed that the average result of student motivation was 55.56% in cycle I, and increased again to 83.33% in cycle II. Meanwhile, the average learning outcomes of the test scores were 77 in cycle I and increased to 93 in cycle II. Thus, it can be concluded that students gain learning experience through the application of Canva-based smart presentations so that they can increase learning motivation